Peran Kepala Adat dalam Meningkatkan Semangat Gotong Royong di Desa Budaya Lung Anai - Zulkifli Zulkifli (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2021)
Gotong royong is a value or habit that was carried out in the previous community which was taught from generation to generation by our ancestors which is something that is mandatory to do. Gotong royong can also foster a sense of togetherness, unity, social solidarity, and participation in development in the village. Currently the culture of gotong royong in Lung Anai Cultural Village is gradually fading away or increasingly being eroded by the times. Even so, there are still people who use this type of gotong royong but it is only familial, not comprehensive to the people of Lung Anai village. The purpose of this study is to find out, analyze, and understand an objective description of how the role of the traditional head in increasing the spirit of mutual cooperation in the Lung Anai cultural village, especially about the role of the Lung Anai cultural village head in increasing the spirit of mutual cooperation. The type of research used in this research is descriptive qualitative research. The research technique is library research, and field research in the form of observations made at the research site, conducting interviews to obtain clearer information according to the needs of the authors in this study. The results of the study indicate and explain that the role of the traditional head in increasing the spirit of mutual cooperation in the Lung Anai Cultural Village, Loa Kulu District, Kutai Kartanegara Regency is in the form of motivation, guidance, direction, supervision, advice, example, and customary sanctions. This role has achieved the optimal goal for the Customary Head in increasing the spirit of mutual cooperation in the Lung Anai Cultural Village. Keywords: The Role of the Traditional Head, Gotong Royong